Persona and Shadow in No Longer Human by Osamu Dazai - Nadia Shafira Yuwananto; Nia Nafisah; Ahmad Bukhori Muslim (Passage, 2022)
Literature is often considered as a form of human expression and experiences. A topic regarding an individual’s experience through their life, including how they face the world around them can be found in a novel written by Osamu Dazai, No Longer Human (1948). Every individual has two sides of personality which can be referred as the Persona and the Shadow. This study focused on identifying and analysing the Persona and the Shadow of Yozo, the main character of No Longer Human. The study was conducted to answer the research questions of how the Persona and the Shadow are portrayed by the characterization of Oba Yozo from No Longer Human. Using Jung’s theory and structuralism, this study found that Yozo’s Persona and Shadow are two opposite personalities and they grow along with him throughout his childhood to adulthood. However, as he gets older, he goes through individuation crisis where the Shadow in him becomes stronger than his Persona. This study is hoped to give a new insight regarding how an individual has two sides of personality and also how an individual goes through individuation crisis. In addition, this study is expected to raise suicidal awareness which now becomes a growing concern in society.